Returns to overeducation and undereducation: evidence for the hospitality sector in Andalusia - Ricardo Pagan; Bienvenido Ortega; Andres J. Marchante (European Regional Science Association (ERSA), 2002)
The objetive of this piece of work is to estimate the returns to overeducation and infraeducation for those people who are working in the hospitality sector in Andalusia. Using a cross-section of workers from a representative survey carried out with European funds (project IFD97-0858), we compare educational attainment of workers and job-required education (reported by workers and managers) in order to obtain a general especification of the earnings function from allocation models of the labor market. These models contain the human capital specification and the job competition specification as special cases. The results show as an earnings especification that includes the possibility of mismatch between educational attainment and requirement is superior to one that only incorporates one or other of the two sides of the matching process. When we use the opinions of workers (managers) about educational requirements, the rate of return to years of adecuate education is 3,27% (3,64%). The rate of returns to overeducation is 1,4% (1,93%) and the penalty for each year of undereducation is 1,81% (2,25%) reduction in wages.
Keywords: 330